THE CORPORATE CRIMES IN DRUG MONEY LAUNDERING: CHASING PROFITS, EVADING JUSTICE? - Nurita, Cut; Siregar, Gomgom TP; Jama, Ahmed Osman (UNISSULA, 2024)
The corporations can now be considered as subjects of criminal law in Indonesia, there is still a lack of clarity in the concept of corporate criminal liability and limited regulations governing the separation of responsibilities between corporations and their managers in criminal cases, including narcotics. The purpose of writing this research is to analyze the position of corporations as subjects of money laundering crimes in Indonesia and to analyze the criminal responsibility of corporations in money laundering crimes from the sale of narcotics. This research is legal research using normative legal research methods. The crime of money laundering in Indonesia, including that derived from the sale of narcotics, can be committed not only by individuals but also by corporations, as regulated in Law No. 8 of 2010 and Law No. 35 of 2009. Although corporations have been recognized as subjects of criminal law, there are differences in the regulations of the two laws, especially in the formulation of sanctions and the clarity of norms regarding criminal liability of corporations in cases of money laundering in the narcotics sector. The novelty of this analysis lies in the identification of regulatory differences in Law No. 8 of 2010 and Law No. 35 of 2009 regarding corporate criminal liability in cases of money laundering from the proceeds of narcotics crimes. In addition, this study highlights weaknesses in the separation of responsibilities between corporations and their managers, which have the potential to hinder the effectiveness of law enforcement.